2018
DOI: 10.1007/s00332-018-9501-y
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic Geometry and Spectral Properties of Classical and Quantum Coupled Angular Momenta

Abstract: We give a detailed study of the symplectic geometry of a family of integrable systems obtained by coupling two angular momenta in a non trivial way. These systems depend on a parameter t ∈ [0, 1] and exhibit different behaviors according to its value. For a certain range of values, the system is semitoric, and we compute some of its symplectic invariants. Even though these invariants have been known for almost a decade, this is to our knowledge the first example of their computation in the case of a non-toric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…This system was originally introduced in Sadovskií & Zĥilinskií [31] and studied in detail in Le Floch & Pelayo [18], where it is shown that there exist two fixed values t − , t + ∈ (0, 1) with t − < t + which depend on R 1 , R 2 such that 1) if t − < t < t + then (J R , H t ) is a semitoric system with exactly one focusfocus point, 2) if t > t + or t < t − the (J R , H t ) is a semitoric system with exactly zero focus-focus points (these are known as systems of toric type, see Section 2 of Vũ Ngo . c [35]), 3) if t = t − or t = t + then (J R , H t ) has a degenerate singular point, and thus is not a semitoric system.…”
Section: 3mentioning
confidence: 99%
See 4 more Smart Citations
“…This system was originally introduced in Sadovskií & Zĥilinskií [31] and studied in detail in Le Floch & Pelayo [18], where it is shown that there exist two fixed values t − , t + ∈ (0, 1) with t − < t + which depend on R 1 , R 2 such that 1) if t − < t < t + then (J R , H t ) is a semitoric system with exactly one focusfocus point, 2) if t > t + or t < t − the (J R , H t ) is a semitoric system with exactly zero focus-focus points (these are known as systems of toric type, see Section 2 of Vũ Ngo . c [35]), 3) if t = t − or t = t + then (J R , H t ) has a degenerate singular point, and thus is not a semitoric system.…”
Section: 3mentioning
confidence: 99%
“…By Equations (18) and (17) we see that X J = ∂ z1 +∂ z2 so the flow of J rotates θ 1 and θ 2 by a common angle. Thus, the S 1 -action produced by the flow of X J preserves the angle difference θ 1 − θ 2 .…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations